2011
DOI: 10.1111/j.1365-2702.2011.03867.x
|View full text |Cite
|
Sign up to set email alerts
|

Agreement in documentation of symptoms, clinical signs, and treatment at the end of life: a comparison of data retrieved from nurse interviews and electronic patient records using the Resident Assessment Instrument for Palliative Care

Abstract: This study contributed to knowledge of agreement between data from nurse interviews and electronic records on symptoms, clinical signs and treatment of dying patients in last three days of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…A total of 65 studies based on 41 706 patients were included in the final analysis. 6 -8,24 -85 Two of the included articles 24,26 were identified from articles’ reference lists. The majority of the studies (45/69%) were prospective (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 65 studies based on 41 706 patients were included in the final analysis. 6 -8,24 -85 Two of the included articles 24,26 were identified from articles’ reference lists. The majority of the studies (45/69%) were prospective (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The retrospective approach made it possible to include older patients who had not accepted that they were approaching end of life, older patients who were too ill to participate in a prospective study and older patients whose terminal state was not recognised by the patients or healthcare workers (Klinkenberg et al, 2004;Hales et al, 2010). Although the validity of symptoms at the end of life collected from EPR may be questioned (Steindal et al, 2012), previous studies indicate that the documentation of pain by healthcare workers appears to be reliable (Teunissen et al, 2007;Steindal et al, 2012). A systematic review, conducted by Teunissen et al (2007), found that the prevalence of symptoms in advanced cancer patients varies among studies using different methods.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The researchers previously assessed agreement between data retrieved from interviews with nurses and data from electronic patient records concerning hospitalised patients' symptoms, clinical signs and treatment during the last 3 days of life (Steindal et al, 2012). In the present article, the variables with moderate or better agreement (kappa 0.41 or higher) were included.…”
Section: Data Collectionmentioning
confidence: 99%